Development and Validation of Stability Indicating UV-Spectrophotometric Method for the Estimation of Hesperidin in Bulk Drugs, Plant Extract, Ayurveda Formulation and Nanoformulation - Chimagave, Supriya Suresh; Jalalpure, Sunil Satyappa; Patil, Akshay Kalgonda; Kurangi, Bhaskar Kallappa (Indian Journal of Pharmaceutical Education and Research, 2022)
Introduction: In present work attempt has been made to develop and validate a simple and sensitive UV spectrophotometric method for estimation of Hesperidin from bulk drugs, plant extract, Ayurveda formulation and novel nanoformulation. Hesperidin is a heteropolycyclic aromatic bioflavonoid found abundance in citrus plants that has been developed into a topical nanoformulation for the treatment of anti-inflammatory activity. It has numerous anti-inflammatory, anti-cancer, and anti-arthritis effects. Objectives: To develop simple, precise, robust, sensitive and accurate UV-Spectrophotometric method for the estimation of hesperidin in bulk drugs, Plant extract, Ayurveda formulation and nanoformulation. Materials and Methods: The optimum condition for the analysis of the drug was established with methanol and water as solvent (1:1). Maximum absorption wavelength was found to be 284 nm with line equation y = 0.0672x +0.003. It showed linear response between the concentration ranges of 2-10 μg/ml. The linear regression coefficient was found to be 0.999. The method was validated for linearity, precision, ruggedness, specificity, sensitivity as per ICH guidelines and all the values of validation was found to be within the acceptance. Conclusion: The developed method was proved to be new, simple, consistent, and accurate it can be used in the pharmaceutical industry as a routine quality control parameter for raw material and formulation.
Keywords: Hesperidin; Stability indicating; UV-Spectrophotometric; Ayurveda; formulation; Nanoformulation